Characterizing co-NL by a group action. (5th December 2014) - AUBERT, CLÉMENT; SEILLER, THOMAS
Abstract : In a recent paper, Girard (2012 ) proposed to use his recent construction of a geometry of interaction in the hyperfinite factor (Girard2011 ) in an innovative way to characterize complexity classes. We begin by giving a detailed explanation of both the choices and the motivations of Girard's definitions. We then provide a complete proof that the complexity classco-NL can be characterized using this new approach. We introduce the non-deterministic pointer machine as a technical tool, a concrete model to compute algorithms.